HUBUNGAN KECERDASAN EMOSIONAL DENGAN HASIL BELAJAR GAMBAR TEKNIK JURUSAN TEKNIK GAMBAR BANGUNAN DI SMK NEGERI 2 PAYAKUMBUH - Raswita Fadhila; Dr. Nurhasan Syah, M.Pd (Universitas Negeri Padang, 2019)
Abstract— This research was motivated by the low learning outcomes of technical drawing subjects in the Department of Building Drawing Engineering at SMK N 2 Payakumbuh. This study aims to determine how much the relationship between Emosional Quotient and learning outcomes of technical drawings. This type of research is quantitative descriptive. The population in this study were students of class XI TGB expertise program at SMK 2 Payakumbuh. The number of students is 51 people from 2 classes. The study sample consisted of all students of class XI TGB totaling 51 people. Sampling uses total sampling. The variables studied were 2 variables. The research instrument used was a questionnaire. The number of statements on the questionnaire are 35 items. Before data collection was carried out, a trial was conducted on class XI students of the TGB expertise program at SMKN 1 Tilatang Kamang, which numbered 21 people. This is done to find out whether the instrument is valid and reliable. Data were analyzed manually and using the SPSS 17.00 application. The result of the correlation coefficient is 0.427 which means it is strong enough, with a level of α 0.002 <0.05 which means significant. Keywords: Emosional Intelegent, The Results of Learning, Technical Drawings